Exploring Entrepreneurial Behavior and Model Innovation of New Ventures via News Communication - Sun, Ningfeng; Zhu, Gang; Song, Hanning; Zhang, Fengrui; Liu, Yuanbing (Frontiers in Psychology, 2021)
The investigation into entrepreneurial behavior and model innovation of new ventures based on news communication aims to reinforce the market competition strength and improve the performance level of new ventures to meet the urgent needs of transformation and upgrading. Based on the theoretical basis of news communication and social cognition theory, a theoretical model is constructed to analyze the relationship between entrepreneurial behavior, innovation mode, and entrepreneurial self-efficacy, to provide reference for the implementation of entrepreneurial behavior of new ventures. Evidently, taking individual factors as antecedent variables to verify their impact on internal entrepreneurial behavior extends the scope of research on corporate entrepreneurship, and also provides significant managerial implications for the promotion of entrepreneurial activities.